Peningkatan Pengetahuan Remaja akan Stunting dan Pola Konsumsi di SMAN 1 Kab Sijunjung - Intan Kamala Aisyiah; Adhyka, Nurmaines; Bun Yurizali (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Stunting is a nutritional problem that threatens the quality of life of the nation's next generation. The complexity of stunting problem, which is a link in the chain, starts with the parents' early knowledge on the importance of consumption patterns. Consumption patterns are important since adolescence in order to prevent the birth of babies with nutritional problems which are the cause of the growth of toddlers with stunting. The initial survey found high rates of stunting in Sijunjung District and there was no primary education by health workers about consumption patterns and how to prevent stunting from teenager. In this socialization, an assessment of knowledge about stunting was carried out by distributing pre-test questionnaires to students, counseling activities and discussion of material regarding stunting and consumption patterns in adolescents, as well as an assessment of students' knowledge after counseling was carried out by distributing post-test questionnaires. The results of this activity showed that there had been an increase in students' knowledge about stunting and consumption patterns. Seeing the enthusiasm of students and the importance of efforts to prevent stunting from adolescence by improving consumption patterns, it is suggested that this event should be carried out by health workers from local health service facilities on a regular basis to all students so that they can reach all adolescents in Sinjunjung Regency.